Faktor-Faktor Yang Mempengaruhi Indeks Pembangunan Manusia Dengan Belanja Daerah Sebagai Variabel Intervening Pada Kabupaten/Kota Di Sumatera Utara - Indri Dithisari; Lia Hartika (Jurnal Riset Akuntansi dan Bisnis, 2022)
The objective of the research was to analyze and find outsome factors whichinfluence IPM (Human Development Index) with Regional Expenditure as intervening variable in districts/towns of North Sumatera. The research used causal method, and the data were gathered by using documentary study and secondary data from the realization of Balance Fund, PAD (Regionally Generated Revenue), BKP (Provincial Financial Aid), Regional Expenditure, and IPM data in the period of 2011-2014. The population was 33 districts/towns in North Sumatera. The gathered data were analyzed by using multiple regression analysis and path analysis. The result of the research showed that, simultaneously, Balance Fund, PAD and BKP had significant influence on Regional expenditure. Partially, Balance Fund had positive but insignificant influence while PAD and BKP had positive and significant influence. It was also found that, simultaneously, Balance Fund, PAD, BKP, BOS (School Operational Aid) Fund, and Regional Expenditure had positive influence on IPM; partially, PAD, BKP, and Regional Expenditure had positive and significant influence on IPM. Balance Fund partially had positive but insignificant influence, while BOS Fund partially had negative and insignificant inluence on IPM. Meanwhile, Regional Expenditure was an intervening variable between Balance Fund and IPM, while for PAD and BKP